Quantifying COVID-19's silver lining: Avoided deaths from air quality improvements in Bogotá - Allen Blackman; Jorge A. Bonilla; Laura Villalobos (Inter-American Development Bank (IDB), 2021)
In cities around the world, Covid-19 lockdowns have improved outdoor air quality, in some cases dramatically. Even if only temporary, these improvements could have longer-lasting effects on policy by making chronic air pollution more salient and boosting political pressure for change. To that end, it is important to develop objective estimates of both the air quality improvements associated with Covid-19 lockdowns and the benefits these improvements generate. We use panel data econometric models to estimate the effect of Bogotás lockdown on fine particulate pollution, epidemiological models to simulate the effect of reductions in that pollution on long-term and short-term mortality, and benefit transfer methods to estimate the monetary value of the avoided mortality. We find that in its first year of implementation, on average, Bogotás lockdown cut fine particulate pollution by more than one-fifth. However, the magnitude of that effect varied considerably over the course of the year and across the citys neighborhoods. Equivalent permanent reductions in fine particulate pollution would reduce long-term premature deaths by more than one-quarter each year, a benefit valued at 670 million per year. Finally, we estimate that in 2020-2021, the lockdown reduced short-term deaths by 31 percent, a benefit valued at 180 million.
Keywords: Q51; Q52; Q53; Q56; Q58; I15; 330; Pollution; COVID-19; lockdown; Colombia; paneldata; integrated exposure-response model; benefit transfer